A core beliefs model of disordered eating: processes and pathways to eating disorder symptomatology - Amaani H. Hatoum; Amy L. Burton; Maree J. Abbott (Journal of Eating Disorders)
Abstract Objective At present there is no clear, cohesive, and comprehensive theoretical understanding of the role of core beliefs in the development of disordered eating. The present study aimed to develop and test a theoretical model outlining important processes and pathways from core beliefs to eating disorder (ED) behaviours. It also aimed to explore potential differences (or similarities) in contributions of four core belief dimensions to the development and maintenance of ED symptomatology. Method Data were collected from a sample of 800 non-clinical participants. Path analysis was conducted to test general and multi-dimensional models. Indirect effects were calculated for all possible pathways from ED core beliefs to dietary restraint, objective binge eating, and compensatory behaviours. Results The hypothesised model demonstrated poor to acceptable fit to the data. Modifications were made to the general model to improve fit, remove non-significant paths and add theoretically and statistically relevant paths. All indirect effects of possible pathways from core beliefs to ED behaviours were significant. A multi-dimensional version of the model was tested with four core belief dimensions. This model identified differences in pathways from each core belief dimension to ED symptoms. Discussion This study extends the current understanding of the role of core beliefs in the development and maintenance of disordered eating, by building upon previous theoretical models and empirical literature. We present a general core beliefs model of disordered eating, and preliminary findings regarding differences in the processes and pathways from four key core belief dimensions to ED behaviours.